Design and Optimization of a Programmable Logic Controller-Based Monitoring System for Machine Parameters in a Frame Assembly Line - Prasetyani, Lin; Ramadhani, Ahmad Fadlan; Setiyadi , Surawan; Hidayat, Muhammad (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2025)
This research addresses the challenge of machine parameter monitoring in the frame assembly line of a motorcycle manufacturing facility. In this process, several machines operate in parallel to integrate key motorcycle components such as engine units, wheels, and body frames. A critical issue identified was that seven machines used standalone controllers that lacked Ethernet communication, limiting real-time monitoring and data acquisition of vital parameters such as status, downtime, and cycle time. To solve this problem, additional programmable controllers were installed using ladder logic programming to retrofit the non-networked machines. These upgrades enabled continuous data transmission and real-time parameter monitoring via a centralized system. The method involved developing a structured architecture capable of collecting, processing, and visualizing machine condition indicators. The research contribution is (1) the successful integration of isolated machines into a unified monitoring network using low-cost PLC retrofitting and (2) the deployment of a register-based monitoring system that supports predictive maintenance through real-time alerts. The system was tested in a live production environment, where more than 80 parameter registers were monitored successfully. Results demonstrated improvements in machine utilization and maintenance response time, with reductions in unplanned downtime and better traceability of machine conditions. The new system improved operational transparency and supported data-driven decision-making for maintenance planning. In conclusion, the implementation of this monitoring system optimized industry 4.0 on the supervision of machine parameters and significantly enhanced production reliability and efficiency in the frame assembly line.